The future of U.S.-India security cooperation - Ganguly, Sumit 1954-; Mason, M. Chris (Manchester University Press, 2021)
"This book deals with the evolution, current status and potential of U.S.-India strategic cooperation. From very modest beginnings, the U.S.-India strategic partnership has developed significantly over the last decade. In considerable part, this growth has stemmed from overlapping concerns about the rise and assertiveness of the People's Republic of China, as well as the instability of Pakistan. Despite the emergence of this partnership, significant differences remain, some of which stem from Cold War legacies, others from divergent global strategic interests and institutional design. In spite of these areas of discord, the overall trajectory of the relationship appears promising. Increased cooperation and closer policy coordination underscore a deepening of the relationship, while fundamental differences in national approaches to strategic challenges demand flexibility and compromise in the future." -- 'Back cover.'
Keywords: Geschichte 2011-2021; Außenbeziehungen; Prognose; Militärische Kooperation; Sicherheitspolitik; USA; Indien; Security, International; United States / Foreign relations / India; India / Foreign relations / United States; United States / Military relations / India; India / Military relations / United States; États-Unis / Relations extérieures / Inde; Inde / Relations extérieures / États-Unis; États-Unis / Relations militaires / Inde; POLITICAL SCIENCE / Public Policy / General; Diplomatic relations; Military relations; India / https://id.oclc.org/worldcat/entity/E39PBJmdx47cDXrRhBXHtbvPwC; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; Aufsatzsammlung